4CPS-064 Evaluation of broad-spectrum beta-lactam prescriptions (except carbapenems) in the military hospital of instruction mohammed V rabat. (March 2019) - Moutaouakkil, Y; Tadlaoui, Y; Atbib, Y; Adouani, B; Bennana, A; Cherrah, Y; Lamsaouri, J; Bousliman, Y
Abstract : Background: The prescription of antibiotics has become one of the most critical acts in hospitals. 1 This is related to the risk of misuse of these drugs and its impact on the development of bacterial resistance and antibiotic inefficiency. Purpose: We aimed to assess broad-spectrum beta-lactam prescriptions (except carbapenems) and the impact of controlled dispensing, antimicrobial management team and antibiotic treatment reassessment in 48–72 hours. Material and methods: This is a descriptive study, which took place on a given day in all hospital units and analysed curative antibiotic broad-spectrum beta-lactam prescriptions. The assessment focused on indication, dosing, combinations, revaluation in 48–72 hours and treatment duration. Results: One-hundred and three prescriptions were identified: amoxicillin (9.70%, n=10), amoxicillin-clavulanic acid (43.69%, n=45), ceftriaxone (33%, n=34), piperacillin-tazobactam (3.88%, n=4), Ceftazidime (7.76%, n=8), and Cefepime (1.94%, n=2). The compliance of the indication, dosage, combinations and re-evaluation at 48–72 hours was satisfactory, respectively 67.96% (n=70), 81.55% (n=84), 82.75% (24/29 associations) and 65.04% (n=67). The compliance of the treatment duration was only 43.68% (n=45). Controlled dispensing showed interest in total antibiotic treatment duration: 76.69% vs. 34.95% compliance for non-controlled dispensed beta-lactams (p=0.02). Conclusion: The prescription or not of broad-spectrum betalactamines is a multifactorial and complex act, but the compliance regarding the duration of treatment could be improved, in particular by a strengthening of the controls of prescriptions. Reference and/or acknowledgements: Didouh M, Cheikh A, Zerhouni MW, et al. Les déterminants de la prescription des antibiotiques à l'hôpital. Revue d'Épidémiol Santé Pub 2018;66:S153. No conflict of interest.